PXR antagonists and implication in drug metabolism. (February 2013) - Mani, Sridhar; Dou, Wei; Redinbo, Matthew R.
<x xml:space="preserve">Abstract</x> Adopted orphan nuclear receptor (NR), pregnane X receptor (PXR), plays a central role in the regulation of xeno- and endobiotic metabolism. Since the discovery of the functional role of PXR in 1998, there is evolving evidence for the role of PXR agonists in abrogating metabolic pathophysiology (e.g., cholestasis, hypercholesterolemia, and inflammation). However, more recently, it is clear that PXR is also an important mediator of adverse xeno- (e.g., enhances acetaminophen toxicity) and endobiotic (e.g., hepatic steatosis) metabolic phenotypes. Moreover, in cancer therapeutics, PXR activation can induce drug resistance, and there is growing evidence for tissue-specific enhancement of the malignant phenotype. Thus, in these instances, there may be a role for PXR antagonists. However, as opposed to the discovery efforts for PXR agonists, there are only a few antagonists described. The mode of action of these antagonists (e.g., sulforaphane) remains less clear. Our laboratory efforts have focused on this question. Since the original discovery of azoles analogs as PXR antagonists, we have preliminarily defined an important PXR antagonist pharmacophore and developed less-toxic PXR antagonists. In this review, we describe our published and unpublished findings on recent structure-function studies involving the azole chemical scaffold. Further work in the future is needed to fully define potent, more-selective PXR antagonists that may be useful in clinical application.